Migrants' Remittances: Channelling Globalization - Remus Gabriel Anghel; Matloob Piracha; Teresa Randazzo (Institute for the Study of Labor (IZA), 2015)
In the past twenty years the ever-growing levels of migrants' remittances made state agencies, international organizations, scholars and practitioners to increasingly consider remittances as one of the main engines to promote globalization and growth in the developing world. By transferring home large amounts of money, information, ideas and practices, migrants and migrant organizations are often seen as able to produce significant changes in countries and localities of origin. Focusing on cases from former socialist countries and around the world, this paper discusses the main debates surrounding the effects and uses of migrant remittances. Furthermore, using different case studies from Europe and Asia, the paper addresses the notion of social remittances, namely the transfers of ideas, practices and norms between societies of origin and destination. It highlights the ideas and practices migrants transfer home, the types of social norms it generates, and the extent to which migration produces transformations in countries of origin.
Keywords: F22; F24; 330; remittances; social remittances; former socialist countries